Enzymatic Polymerisation - Palmans, Anja R. A.; Palmans, Anja R. A.; Heise, Andreas.; Heise, Andreas. (Advances in Polymer Science,, 2011)
Oxireductases in the Enzymatic Synthesis of Water-Soluble Conducting Polymers, by E. Ochoteco and D. Mecerreyes * Transferases in Polymer Chemistry, by J. van der Vlist and K. Loos * Hydrolases Part I: Enzyme Mechanism, Selectivity and Control in the Synthesis of Well-Defined Polymers, by M.A.J. Veld and A.R.A. Palmans * Hydrolases in Polymer Chemistry: Chemoenzymatic Approaches to Polymeric Materials, by A. Heise and A.R.A. Palmans * Hydrolases in Polymer Chemistry: Part III: Synthesis and Limited Surface Hydrolysis of Polyesters and Other Polymers, by G.M. Guebitz * Exploiting Biocatalysis in the Synthesis of Supramolecular Polymers, by S. Roy and R. V. Ulijn.